THE DEVELOPMENT OF SOCIAL MEDIA (FACEBOOK) GUIDELINE: VISIBILITY ELEMENT TOWARD SMALL MEDIUM ENTERPRISE (SME’S) ENTREPRENEUR - Mohd Hafizie Suhaimi; Norshuhada Shiratuddin (JOURNAL INFORMATION AND TECHNOLOGY MANAGEMENT (JISTM), 2016)
Nowadays, social media become phenomenon in the business environment. Marketing technology through social media can be used by SME entrepreneurs in particular to ensure that marketing activity is enhanced. Indirectly it is expected to positively impact the visibility of SME entrepreneurs. Visibility is defined as the ability of an organization to be seen in the great community of the role and capabilities. It has unique and specific features to attract the attention of consumers. The study concludes that the visibility is divided into five elements, namely (1) a construction site a prominent business, (2) formation of community, (3) updated management of information content; (4) Analysis of customer behavior, and (5) optimization opportunities market. Basic elements of development are developed based on three main theories of the new communication paradigm theory, social influence theory and the theory of enrichment media. In general, the visibility factors for SME entrepreneurs are expected to strengthen the company’s marketing. Thus, the visibility elements will encourage and guide the SME entrepreneurs to optimize social media as competitive marketing tool